INCREASING STUDENT LISTENING COMPREHENSION USING STORYTELLING: AN ACTION RESEARCH AT THE SECOND YEAR OF SMK HARAPAN KARTASURA - MURJANI, WAHYU TRI (2010)
This research paper is aimed at describing the process of teaching listening using storytelling at the second year of SMK Harapan Kartasura. A preliminary observation in this research showed that the mastery of English listening of the students was still low, because the students’s score in the listening test was also low. The students have less motivation to follow the listening lesson. They don’t like the English listening lesson, because they think that the listening lesson makes them bored and that material is not interesting.